Long overlooked: Adult VACTERL association unmasked by a large patent ductus arteriosus - Aravindharaj Tamilselvan, MBBS, MD; Machaiah Kallumadanda Mohan, MBBS, MD (Radiology Case Reports)
VACTERL associations are typically diagnosed in neonates and infants, with adult presentations being rare. This case report presents an adult patient diagnosed with VACTERL association following the discovery of a significant patent ductus arteriosus.